PENGARUH ADOPSI INTERNASIONAL FINANCIAL REPORTING STANDARD (IFRS), LEVERAGE, DAN PROFITABILITAS TERHADAP KUALITAS LABA - Fanni Monada Essa Putri; Immawan Azhar Ben Atasoge; Imam Asrofi; Avita Avita (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2021)
Abstract: The purpose of this study is to explain the effect of international financial reporting standards adoption, leverage, profitability on profit quality, this type of research uses quantitative research using annual data. The population used is companies listed on the Indonesia stock exchange that adopted and have not adopted IFRS in the period 2015-2019. The regression used is OLS (Ordinary Least Square) by taking a sample of 14 companies listed on the Indonesia stock exchange. The results of this study showed that from the ifrs variable, leverage, and profitability only ifrs variables had a significant effect on the quality of profit in 14 companies on the Indonesia Stock Exchange. Keywords: IFRS; leverage; Profit Quality.